Posterior Mediastinal Adenomatoid Tumor: A Case Report and Review of the Literature - Vishwas Parekh; Thomas Winokur; Robert J. Cerfolio; Todd M. Stevens (Case Reports in Pathology)
Adenomatoid tumor is an uncommon benign neoplasm of mesothelial differentiation that distinctively arises in and around the genital organs. In rare instances, it has been described in extragenital locations. There have been only two reports documenting its occurrence in the anterior mediastinum, and no reports documenting its occurrence in the posterior mediastinum. We report the first case of posterior mediastinal adenomatoid tumor. A 37-year-old Caucasian woman presented with symptoms of bronchitis. Imaging studies identified a 2.0 cm posterior mediastinal mass abutting the T9 vertebral body, clinically and radiologically most consistent with schwannoma. Histologic sections revealed a lesion composed of epithelioid cells arranged in cords and luminal profiles embedded in a fibrotic to loose stroma and surrounded by a fibrous pseudocapsule. Lesional cells showed vacuolated eosinophilic cytoplasm and peripherally displaced nuclei with prominent nucleoli. There was focal cytologic atypia but no mitotic figures or necrosis was identified. The lesional cells expressed cytokeratin, calretinin, and nuclear WT1 but were negative for PAX8, TTF1, p53, chromogranin, CD31, and CD34, and Ki67 showed <2% proliferation rate, diagnostic of adenomatoid tumor. Three years after resection, the patient is in good health without tumor recurrence. Thus, our encounter effectively expands the differential diagnosis of posterior mediastinal neoplastic entities.